PROBLEM-BASED LEARNING MODEL MANAGEMENT ON THE INTEREST IN LEARNING MATHEMATHICS OF ELEMENTAR SCHOOL STUDENT - Deni Setiawan; Indah Anggraini; Arif Hidayat (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2023)
The Problem Based Learning (PBL) model can be applied to elementary mathematics learning. This study aims to analyze the factors of student interest, the learning process, and the applications of PBL in elementary school mathematics learning. The research used qualitative method with a case study approach. The research subjects were students and teachers of class V SD Negeri 1 Bengkal. Researchers collected data through structured interviews with mathematics teachers, filling out 15 student questionnaires, learning observations, and photo, audio, and video documentation. Miles and Huberman's model analysis techniques include data reduction, data presentation, and conclusions. Design of data validity with credibility test and confirmability test. The credibility test uses methods of increasing research persistence, technique triangulation, and member check. The Confirmability test uses journals to reflect data. Research findings (1) two factors influence interest in learning, namely internal and external factors in mathematics leaning. (2) The learning process of the PBL model in mathematics leaning is student-oriented. (3) Learning with the PBL model has advantages, including increasing learning motivation; improving student academic achievement; improving the ability to collaborate, work together and communicate.